The Impact of Video-Based Learning to Cognitive Learning Outcome of Student in Elementary School - Ismiyanti, Yulina; Permatasari, Devi; Mayasari, Novi; Qoni’ah, Marifatul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The results of observations and interviews at elementary school showed that Indonesian history material was considered material that was difficult for students to accept and understand. The purpose of this study is to determine the effect of video based learning on cognitive learning outcomes of Indonesian history material in elementary schools. This research method is an experiment. The form of the experimental design used in this study was a quasi-experimental design with a nonequivalent control group type. Data analysis was carried out through tests for normality, homogeneity, paired sample t-test, and independent sample t-test. The first hypothesis test, namely the paired sample t-test, shows that there is an influence seen from Lower and Upper which is negative, namely Upper is -18.270 and Lower is -27.312. Sig. Value (2-tailed) shows the number 0.000 which means <0.05. The second hypothesis test, namely the independent sample t-test, shows that there is a difference seen from Lower and Upper which is negative, namely Lower is -13.651 and Upper is -3.109. Sig. Value (2-tailed) shows the number 0.002 which means <0.05 then Ho is rejected and Ha is accepted. It was concluded that the video based learning had an effect on the cognitive learning outcomes of Indonesian historical material at SDN 02 Temulus. Videos based learning can be used as an alternate learning resource in elementary schools to help students comprehend Indonesian history.